Prevalence of Early Sexual Debut among Young Adolescents in Ten States of the United States - Sadandaula R. Muheriwa-Matemba; Elizabeth Anson; Holly A. McGregor; Chen Zhang; Natasha Crooks; Natalie M. LeBlanc (MDPI AG, 2024)
Sexual debut among young adolescents is under-investigated. In this quantitative descriptive study, we examined the 2019 Middle School Youth Risk Behavior Survey (YRBS) data of 66,366 young adolescents aged 10-14 from 10 states to determine the prevalence of early sexual debut among young adolescents. Data analyses used state-level sampling weights as described in the CDC's 2019 Middle School YRBS user guide. Nearly 8% of the sample reported having had sexual intercourse. Of those who reported age of first sex, 4% had their first sexual intercourse before 13 years of age. Compared to Whites, young Black/African American (13.2% vs. 5.1%, OR = 4.51, 95% CI: 2.78-7.31) and Hispanic adolescents (8.3 % vs. 5.1 %, OR = 1.44, 95% CI = 1.13-1.84) were more likely to report having early sexual intercourse. Males were more likely to report having multiple sexual partners than females (48.1% vs. 36.5%, OR = 1.68, 95% CI = 1.22-2.29) and were more likely to report using condoms during their last sexual intercourse compared to their female counterparts (59.7% vs. 50.8%, OR = 1.43, 95% CI = 1.06-1.94). This study suggests the need for more research on young adolescents' sexual behaviors and for the development of sexual health interventions that target young adolescents.